Brucella abortus Requires the Heme Transporter BhuA for Maintenance of Chronic Infection in BALB/c Mice - Paulley, James T. (American Society for Microbiology (ASM), 2007)
The gene annotated BAB2_1150 in the Brucella abortus 2308 genome sequence is predicted to encode a homolog of the well-characterized heme transporter ShuA of Shigella dysenteriae and accordingly has been given the designation bhuA (Brucella heme utilization). Phenotypic analysis of an isogenic bhuA mutant derived from B. abortus 2308 verified that there is a link between BhuA and the ability of the parent strain to use heme as an iron source in in vitro assays. Maximum expression of bhuA in B. abortus 2308 is observed during stationary phase when this strain in cultivated in low-iron minimal medium, and a comparison of the growth characteristics of the B. abortus bhuA mutant and 2308 in this medium suggested that heme serves as an important iron source for the parent strain during stationary phase. The B. abortus bhuA mutant HR1703 exhibits significant attenuation in cultured murine macrophages compared to strain 2308, and unlike its parent strain, the B. abortus bhuA mutant is unable to maintain a chronic spleen infection in experimentally infected BALB/c mice. These experimental findings suggest that heme and/or heme-containing proteins represent important iron sources for B. abortus 2308 during its residence in the mammalian host and that BhuA is required for efficient utilization of these iron sources.